2012
DOI: 10.1166/msr.2012.1015
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium Concentrations Regulated by Cyclic ADP-Ribose and Heat in the Mouse Hypothalamus

Abstract: Oxytocin (OT) is synthesized and released in the hypothalamus, and plays a critical role in social recognition and behavior in mammals. Brain OT release is largely due to elevation of intracellular cytosolic calcium concentrations ([Ca 2+ ] i ) induced by mobilization of Ca 2+ from Ca 2+ pools by cyclic ADP-ribose (cADPR) catalyzed by the ADPribosyl cyclase activity of CD38. Recently, we reported that extracellular application of cADPR, together with heat, increased [Ca 2+ ] i in cultured neuronal tumor cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Other types of voltage-dependent Ca 2+ channels are also involved in oxytocinergic neurons (Tobin et al, 2011). Recently, we showed that OXT release is also sensitive to hyperthermia and Ca 2+ influx via TRPM2 channels (Amina et al, 2010; Liu et al, 2012a). …”
Section: Oxytocin and Cyclic Adp-ribosementioning
confidence: 99%
“…Other types of voltage-dependent Ca 2+ channels are also involved in oxytocinergic neurons (Tobin et al, 2011). Recently, we showed that OXT release is also sensitive to hyperthermia and Ca 2+ influx via TRPM2 channels (Amina et al, 2010; Liu et al, 2012a). …”
Section: Oxytocin and Cyclic Adp-ribosementioning
confidence: 99%
“…We cannot exclude the possibility that CD38 may act as a binding partner of M-channels or other types of ion channels, because it has recently been shown that CD38 and TRPM2 are co-immunoprecipitated and functionally interact and that CD38 acts as an activating element for hypertonicity-induced cation channels and TRPM2 channels in cell proliferation or hypertonic volume response of cells (Numata et al, 2012). We also showed that TRPM2 channels are involved in cADPR-induced [Ca 2+ i increases in NG108-15 cells , which may explain hyperthermia-induced [Ca 2+ i increases in the hypothalamus (Liu et al, 2012). Therefore, it is of interest to examine whether TRPM2 also contributes to mAChR signaling.…”
Section: Discussionmentioning
confidence: 52%
“…Subsequently, in isolated hypothalamic neurons, application of 100 pM OT results in [Ca 2+ ] i increases: a rapid initial increase and a sustained elevation lasting for 5 min [ 69 ]. OT elicits an initial elevation of the maximum [Ca 2+ ] i , and this phase is IP 3 -dependent.…”
Section: Effects Of Oxytocin On Adp-ribosyl Cyclase and Intracellularmentioning
confidence: 99%
“…Pretreatment with 8-bromo-cADPR, an antagonist of the cADPR-binding site of Ca 2+ release channels of ryanodine, inhibits OT-mediated sustained [Ca 2+ ] i increases. ADPR and β-NAD + also induce elevation of [Ca 2+ ] i and replicate the second phase of sustained [Ca 2+ ] i increases [ 49 , 69 ]. Under Ca 2+ -free conditions, the OT-mediated increase of [Ca 2+ ] i shows little change in either phase, suggesting that the two phases of [Ca 2+ ] i elevation in hypothalamic neurons are due to Ca 2+ mobilization from the intracellular Ca 2+ pools [ 49 ].…”
Section: Effects Of Oxytocin On Adp-ribosyl Cyclase and Intracellularmentioning
confidence: 99%